Conversions and politics of Hindu right - Sarkar, Sumit (1999)
With the spread of liberation theologies, churches have been changing. Christian groups have been prominent in progressive movements. In the face of attacks, they have not retreated into sectarian or fundamentalist shells but have joined secular, liberal and Left formations. It is this progressive aspect of contemporary Christianity that arouses the greatest anger and fear among proponents of hindutva. - Reproduced
Keywords: Religious conversion - India; Religious conversion